Effects of yoga on well-being and healthy ageing: study protocol for a randomised controlled trial (FitForAge). Issue 5 (29th May 2019) - Östh, Josefine; Diwan, Vinod; Jirwe, Maria; Diwan, Vishal; Choudhary, Anita; Mahadik, Vijay Khanderao; Pascoe, Michaela; Hallgren, Mats
Abstract : Introduction: Due to ageing populations worldwide, the burden of disability is increasing. It is therefore important to develop interventions that improve healthy ageing, reduce disability onset and enhance life quality. Physical activity can promote healthy ageing and help maintain independence, yet many older adults are inactive. Yoga is a form of physical activity that aims to improve health and may be particularly suitable for older adults. Research indicates positive effects of yoga on several health-related outcomes; however, empirical studies examining the benefits of yoga on well-being among the elderly remain scarce. This study protocol reports the methodology for a 12-week yoga programme aimed to improve health and well-being among physically inactive older adults. Methods and analysis: Three group parallel, single-blind randomised controlled trial. Two comparison groups are included: aerobic exercise and a non-active wait-list control. In total, 180 participants aged 65–85 years will be recruited. Assessments will be performed at baseline and postintervention (12-week follow-up). The primary outcome is subjective well-being. Secondary outcomes include physical activity/sedentary behaviour, mobility/fall risk, cognition, depression, anxiety, mood, stress, pain, sleep quality, social support and cardiometabolic risk factors. Data will be analysed using intention-to-treat analyses, with mixed linear modelling. Ethics and dissemination: This study is approved by the Ethical Review Board in Stockholm (2017/1862-31/2). All participants must voluntarily agree to participate and are free to withdraw from the study at any point. Written informed consent will be obtained from each participant prior to inclusion. Results will be available through research articles and conferences. A summary of key results will be publicly available through newspaper articles. Trial registration number: DRKS00015093, U1111-1217-4248